HUBUNGAN PEMBERIAN MP-ASI DENGAN STATUS GIZI BAYI 6-11 BULAN DI WILAYAH KERJA PUSKESMAS SAMBAU KOTA BATAM - Ibrahim, Ibrahim; Isramilda, Isramilda; Permatasari, Siska Dwi (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2023)
Background: the nutritional status of infants greatly influences their growth and development. To find out the nutritional status of infants can be seen from what they consume. Babies aged 6-11 months get nutrition from MP-ASI and ASI. The purpose of this study was to determine the relationship between complementary feeding and nutritional status at the Sambau Health Center. Method: Type of quantitative research with a cross-sectional study design. This research was conducted in December 2022. The population was infants aged 6-11 months who attended Posyandu activities in December as many as 69 people were taken using the total sampling technique. Data on MP-ASI administration, frequency, and form of MP-ASI were obtained using a questionnaire and measuring weight/PB. The data were analyzed using the chi-square test. Results: Giving MP-ASI to infants 6-11 months was 63.8%. The frequency of giving MP-ASI was mostly according to age, namely 75.4%. Most of the MP-ASI forms are age-appropriate, namely 76.8%. The nutritional status of infants aged 6-11 months is mostly good, namely 92.8%. The results of the chi-square test obtained a p-value of 0.856 for the relationship between MP-ASI and nutritional status, and the relationship between MP-ASI frequency and nutritional status obtained a p-value of 0.003. Meanwhile, the relationship between complementary feeding and nutritional status obtained a p-value of 0.861. Conclusion: There is no significant relationship between the provision of MP-ASI and the nutritional status of infants 6-11 months at the Sambau Health Center with a value of p=0.586 (p>0.05).